2018
DOI: 10.1002/asia.201800788
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Self‐Healing Supramolecular Nucleoside Hydrogel Based on Guanosine and Isoguanosine

Abstract: Recently, supramolecular hydrogels have attracted increasing interest owing to their tunable stability and inherent biocompatibility. However, only few studies have been reported in the literature on self-healing supramolecular nucleoside hydrogels, compared to self-healing polymer hydrogels. In this work, we successfully developed a self-healing supramolecular nucleoside hydrogel obtained by simply mixing equimolar amounts of guanosine (G) and isoguanosine (isoG) in the presence of K . The gelation properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Another possibility is to formulate the gel with metal ions such as silver (Ag + ), which increases the sta bility (from hours to months) and the storage moduli (up to 8 kPa) and endows the resulting gel with thixotropy 110 . Addition of isoguanosine is another alternative to turn guanosine gels into thixotropic cogels exhibiting very short recovery times (<20 s) 111 .…”
Section: Wwwnaturecom/natrevchemmentioning
confidence: 99%
“…Another possibility is to formulate the gel with metal ions such as silver (Ag + ), which increases the sta bility (from hours to months) and the storage moduli (up to 8 kPa) and endows the resulting gel with thixotropy 110 . Addition of isoguanosine is another alternative to turn guanosine gels into thixotropic cogels exhibiting very short recovery times (<20 s) 111 .…”
Section: Wwwnaturecom/natrevchemmentioning
confidence: 99%
“…Moreover, while binding affinity studies have been done among either monovalent cations or divalent cations, very few studies have been shown to compare energy and binding selectivity between these two types of charged cations, likely due to the complexity of the overall assembly . Thus, understanding how cations interact with G 4 ‐quartets is one of the fundamental tasks for construction of well‐defined G‐quadruplexes for potential applications . Herein, we report the detailed investigations on cation selectivity between two reported and well‐characterized G‐quadruplexes supramolecular systems, the anion bridged G 16 and anion‐binding‐free G 8 assembly (based on G‐monomer conformation control).…”
Section: Methodsmentioning
confidence: 99%
“…[25,26] Thus, understanding how cations interact with G 4 -quartets is one of the fundamental tasks for construction of well-defined G-quadruplexes for potential applications. [27][28][29][30][31][32] Herein, we report the detailed investigations on cation selectivity between two reported and well-characterized G-quadruplexes supramolecular systems, the anion bridged G 16 [33] and anion-binding-free G 8 assembly (based on G-monomer conformation control). 34 The interesting reversed binding ability between mono-valent K + and divalent Ba 2 + was revealed.…”
mentioning
confidence: 99%
“…This has drawn attention to isoG, an isomer of G. However, the injection of isoG hydrogels is challenging. 159 Recently, inspired 159 et al successfully constructed a self-healing supramolecular co-hydrogel in 2018 by simply mixing G and isoG with 1 : 1 and 1 : 3 molar ratios in the presence of K + . In terms of ion dependence, both mixtures can form co-gels in the presence of K + and Rb + .…”
Section: Isog-based Supramolecular Hydrogelsmentioning
confidence: 99%